Virtual Education in the critical thinking of university students - Valencia Morocho, Carlos Arturo (2021)
The goal was to determine the influence generated by virtual education on the critical thinking of students during the pandemic. The design incorporated positivist paradigm, applied type, explanatory level, quantitative approach, hypothetical-deductive method and quasi-experimental design elements. The sample was non-probabilistic and consisted of 68 students, divided into an experimental group with 35 students, and a control group with 33 students. Both groups were given a pre-test composed of 20 items with argumentative texts, in order to evaluate their critical thinking. The control group was administered traditional teaching in virtual mode, and the experimental group the virtual teaching program through the discussion forum. A similar test was applied to both groups in the post-test phase. Following the application of the program, the results obtained by means of the Mann Whitney U test (81.00, Z= -6.142< .05) were significant. Conclusion: Virtual education significantly influences critical thinking.